Patient and Specimen Identification in Laboratory Unit of PKU Muhammadiyah Gamping Hospital - Siti Shofiah; Sri Sundari; Qurratul Aini (Jurnal Admmirasi, 2018)
Laboratory is one of the main supporting departemen in hospital services.This study aims to determine the implementation of patient and specimens identification based on SOP (standard operating procerude) in laboratory departemen. This research used mixed methods research which are quantitative and qualitative method. Quantitative data obtained by moment observation using check list and qualitative data obtained by interview. The implementation of patient identification and specimen in the laboratory of PKU Muhammadiyah Gamping Hospital has not fully complied with SOP. According to 100 moment observation, patient data on the laboratory request form is 77% incomplete, 74% laboratory officers confirmed the patient's identity correctly, 84% laboratory officers verified the name and date of birth of the patient and only 45% laboratory officers placed the verified labels on the specimen tube simultaneously with the patient's presence. Barriers in the implementation are less of culture in the patient safety especially patient and specimen identification, uncomplete in the request form, the number of requests for laboratory examination and less of evaluation. Hospitals should provide maximum support to the application of patient safety culture, provide adequate numbers of health personnel, improvement of facilities and infrastructure, policy improvement, training, and evaluation.